Factors Affecting Delays in Retrieval of Inpatient Medical Record Filesat the West NTB Provincial Hospital - Yanti, Ni Komang Wijiani; Yulianti, Mega Sara (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Every patient comes to visit a health care facility for health service needs so that medical record files must always be available, but medical record files often experience delays in returning them. Delays in the retrieval of inpatient medical record files were caused by duplicate medical record files, incorrectly stored, and not completed by the inpatient doctor. The aim of this study was to determine the factors that influence the delay in the retrieval of inpatient medical record files at the NTB Provincial Hospital. The type of research used is quantitative with cross sectional design. The population in this study were all medical record officers at the NTB Provincial Hospital, totaling 45 people with a total sample of 6 retrieval officers. The sampling technique uses incidental sampling. Data collection was carried out by observing or observing all medical record file retrieval officers using a check list. Data processing is done by editing, coding, data entry, and cleaning. Analysis of the data used is descriptive quantitative analysis. The results of the study based on the medical record file officers were categorized as good 0 (0%), and as many as 3 people (50%) categorized as sufficient, while the medical record file officers were categorized as lacking as many as 3 people (50%). The results of the study based on medical record files were categorized as good with a total of 0 (0%), and categorized as sufficient with a yes answer of 10 items (71.4%), while medical record files were categorized as lacking with 4 items (28.6%). It is necessary to increase medical record officers, especially officers in filing, so that their accuracy is increased in separating medical record numbers before storing them so that medical record files are not misplaced so that services at the hospital run smoothly.